Balancing Ecosystems, Harvests, and Seafood Markets. Issue 10 (24th August 2022) - Collie, Jeremy; Schumann, Sarah; Masury, Kate; Uchida, Hirotsugu; Collie, Claire
Abstract : Recognition of competition and predator–prey interactions among species has led some to promote the concept of balanced harvesting, whereby fisheries would remove a proportional, sustainable fraction of all species in the fish community. Practical implementation of such a strategy hinges on understanding the current degree of species selection in fisheries and the factors that drive this selection. This interdisciplinary study measured ecosystem–market symmetry in the New England region by tracking species composition from ecosystem production, to catch, landings, and seafood markets. Strong species selection occurred in the catch and in seafood markets but not by discarding, which suggests that that requiring full retention of all species caught may make a limited contribution to promoting ecosystem–market symmetry. Results from a group of citizen scientists indicate that higher priced species were generally more available in seafood markets and that availability diminished rapidly with distance from shore. We conclude that market‐based selection may be reduced through a combination of locavore consumer education and global marketing strategies.